An interventional analysis of the combined effects of five-finger relaxation and aromatherapy on sleep quality among breast cancer patients - Heriani, Novia; Mariani, Mariani; Negara, Candra Kusuma (Science Midwifery, 2025)
Sleep disturbances and anxiety are two common complaints experienced by breast cancer patients undergoing chemotherapy. Non-pharmacological approaches have emerged as important strategies to improve patients’ overall quality of life in a holistic manner. This study aimed to evaluate the effectiveness of combining the five-finger relaxation technique and aromatherapy in improving sleep quality and reducing anxiety levels among breast cancer patients undergoing chemotherapy. A quasi-experimental design with a pretest-posttest control group approach was employed. A total of 30 participants were equally divided into two groups (intervention and control). The intervention was administered over a two-week period and consisted of five-finger relaxation training and the use of lavender essential oil aromatherapy before bedtime. The instruments used were the Pittsburgh Sleep Quality Index (PSQI) and the Hamilton Anxiety Rating Scale (HARS). The analysis revealed a significant decrease in PSQI scores (p = 0.021) and HARS scores (p = 0.037) in the intervention group, whereas no significant changes were observed in the control group. These findings indicate that the combined intervention is effective in improving sleep quality and reducing anxiety. This intervention is recommended as an applicable complementary therapy that can be integrated into nursing practice, particularly in supportive care for cancer patients.